EVALUASI PENGGUNAAN PARASETAMOL INFUS PADA PASIEN RAWAT INAP DI RSUD GAMBIRAN KEDIRI - , YUYUN PUSPOSARI, Dr. Arief Nurrochmad, M.Si., M.Sc., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Intravenous (i.v) paracetamol is a new drug formulation that is nowadays, available in Indonesia. The i.v paracetamol formulation is indicated for short-term treatment of moderate pain, especially following surgery, and for short-term of fever